Quality of Life in Patients With Cushing's Disease - Santos, Alicia; Resmini, Eugenia; Martínez Momblán, Mª Antonia; Valassi, Elena; Martel, Luciana; Webb, Susan M. (Frontiers in Endocrinology, 2019)
Cushing’s disease (and by extension, Cushing’s syndrome) is a rare disease due to a chronic cortisol excess, which usually has an important impact on quality of life (QoL). It can lead to numerous comorbidities that can interfere with daily life, as fatigability, myopathy, bone loss and fragility, increased cardiovascular risk, depression and cognitive alterations. Of note, psychological alterations (including depression and anxiety) occur often, and are an important determinant of impaired quality QoL. QoL scores using different questionnaires are poorer in comparison to healthy controls, other pituitary adenomas and some chronic diseases. Even if some improvements can be observed after successful treatment, recovery does not seem to be complete, and comorbidities persist. This persistent QoL impairment has been found using both generic and disease-specific QoL questionnaires, and is also reported by the patients themselves, when asked directly. Multidisciplinary teams are essential to improve patients’ well-being. Clinicians should take into account the whole scope of clinical problems and address the different comorbidites associated with the disease. Screening in the psychological sphere, with further intervention if necessary, can be helpful in the management of these patients. Interventions and programs have shown promising results, although there is a need for further development of new strategies for the benefit of these patients.